2015
DOI: 10.1038/ncomms9755
|View full text |Cite
|
Sign up to set email alerts
|

MITF and c-Jun antagonism interconnects melanoma dedifferentiation with pro-inflammatory cytokine responsiveness and myeloid cell recruitment

Abstract: Inflammation promotes phenotypic plasticity in melanoma, a source of non-genetic heterogeneity, but the molecular framework is poorly understood. Here we use functional genomic approaches and identify a reciprocal antagonism between the melanocyte lineage transcription factor MITF and c-Jun, which interconnects inflammation-induced dedifferentiation with pro-inflammatory cytokine responsiveness of melanoma cells favouring myeloid cell recruitment. We show that pro-inflammatory cytokines such as TNF-α instigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
203
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 187 publications
(220 citation statements)
references
References 70 publications
16
203
0
1
Order By: Relevance
“…Smith et al (2014) reported that TNFα promotes melanoma growth and therapeutic resistance by up-regulating MITF, which should promote differentiation. In contrast, other studies report that TNFα down-regulates MITF (Landsberg et al 2012;Konieczkowski et al 2014;Riesenberg et al 2015), decreases differentiation, and promotes a slow-cycling phenotype (Ostyn et al 2014), a characteristic of MITF-low cells (Cheli et al 2011b). Significantly, a recently described melanoma TNFα response gene set (Riesenberg et al 2015) positively correlated with the GSS score in the TCGA melanoma cohort as well as the single-cell RNA-seq patient-derived melanoma data from Tirosh et al (2016) (Fig.…”
Section: Inhibition Of Eif2b Drives Invasivenessmentioning
confidence: 88%
See 2 more Smart Citations
“…Smith et al (2014) reported that TNFα promotes melanoma growth and therapeutic resistance by up-regulating MITF, which should promote differentiation. In contrast, other studies report that TNFα down-regulates MITF (Landsberg et al 2012;Konieczkowski et al 2014;Riesenberg et al 2015), decreases differentiation, and promotes a slow-cycling phenotype (Ostyn et al 2014), a characteristic of MITF-low cells (Cheli et al 2011b). Significantly, a recently described melanoma TNFα response gene set (Riesenberg et al 2015) positively correlated with the GSS score in the TCGA melanoma cohort as well as the single-cell RNA-seq patient-derived melanoma data from Tirosh et al (2016) (Fig.…”
Section: Inhibition Of Eif2b Drives Invasivenessmentioning
confidence: 88%
“…The moving average expression of individual genes of interest or averaged signatures were calculated using a sample window size of n = 20, and trend lines were added to the bar plots. An R-skript for calculating and generating moving average plots of TCGA cancer cohorts implementing TCGA access via cBioportal was provided in our previous study (Riesenberg et al 2015). Significance of the Spearman rank correlation was determined by an asymptotic Spearman correlation test using the original log 2 expression values and not the moving average values.…”
Section: Tcga Transcriptomic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…49 MITF also repressed ZEB1 transcription in the 501mel human melanoma cell line, 50 as well as inflammation genes through repressing c-Jun expression in mouse and human melanoma cell lines. 51 MITF recruits RBPJK as a cofactor in repressing transcription of microRNAs miR-221 and miR-222 in human melanoma cell lines. 52 It remains mechanistically unclear how MITF represses target genes and what functional roles MITF has through repressing gene expression.…”
Section: Mitf Target Genesmentioning
confidence: 99%
“…46,47 Furthermore, repression of MITF expression could make melanoma to recruit myeloid immune cells into the tumor microenvironment which could counteract tumor growth promoting and immunosuppressive functions. 48 Besides, MITF was related to intrinsic drug resistance and the drug resistance to BRAF inhibitors in melanoma cells, which could further promote cell survival and proliferation. 49,50 Melanoma cells expressing MITF highly displayed significant drug resistance in BRAF-i and MEK-i treatment.…”
mentioning
confidence: 99%